Resilience: a transversal occupational skill for current organizations - Piñeros-Botero, María del Rosario (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2013)
This paper presents a structural and functional analysis of the resilience as transversal occupational skill, which is consequence of concern about the social, economical and political crisis that currently affects the organizations. It is explained a brief concept of resilience from different knowledge areas such as social science, physics, sociology and administration, among others. The analysis is based on some studies related to deal the resilience from the transverse occupational skills and the MCclelland approach TO KNOW TO BE AND TO KNOW TO DO, as a structural base for behavior and performance of people. Finally we propose an organizational resilience model that presents its functionality and categorization of profiles in occupational and individual skills that allow encouraging cultural and organizational behavior by means of optimization strategies to current organizations. The term organizations, is going to be used to talk about an industry or enterprise of any kind or financial sector.